2007
DOI: 10.1055/s-2006-924360
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music during Warm-Up on Consecutive Anaerobic Performance in Elite Adolescent Volleyball Players

Abstract: Music is believed to improve athletic performance. The aim of the present study was to determine the effect of arousing music during warm-up on anaerobic performance in elite national level adolescent volleyball players. Twenty-four players (12 males and 12 females) performed the Wingate Anaerobic Test following a 10-minute warm-up with and without music (two separate occasions, random order). During warm-up with music, mean heart rate was significantly higher. Following the warm-up with music, peak anaerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
111
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(139 citation statements)
references
References 17 publications
(31 reference statements)
11
111
7
1
Order By: Relevance
“…Since Western music is very popular in our country, this CD is used frequently in health clubs, schools and sports colleges for aerobic training, and thus also fulfills the criteria of the music's suitability to socio-cultural background and strong association to sport. We have previously demonstrated that listening to selected tracks from this CD (ranked by the participants as a device to increase activity) during warm-up improved peak anaerobic power in elite adolescent volleyball players [13]. Paired t-test was used to determine differences in ideal sprint time, total sprint time, performance decrement, heart rate and RPE, between RST with and without music.…”
Section: Music Selectionmentioning
confidence: 99%
“…Since Western music is very popular in our country, this CD is used frequently in health clubs, schools and sports colleges for aerobic training, and thus also fulfills the criteria of the music's suitability to socio-cultural background and strong association to sport. We have previously demonstrated that listening to selected tracks from this CD (ranked by the participants as a device to increase activity) during warm-up improved peak anaerobic power in elite adolescent volleyball players [13]. Paired t-test was used to determine differences in ideal sprint time, total sprint time, performance decrement, heart rate and RPE, between RST with and without music.…”
Section: Music Selectionmentioning
confidence: 99%
“…In contrast, Ferguson and colleagues (1994) demonstrated that both types of music (fast and slow) can improve performance in karate training (Ferguson, Carbonneau, Chambliss, 1994). Eliakim and colleagues (2007) study the effects of listening to music at 140 beats per minute during the warm-up began and the results showed that music can yield a significant effect during the Wingate test (Eliakim et al, 2007). Karageorghis and colleagues (2009) test for anaerobic Wingate to measure the elite volleyball players use, these individuals when exposed to favorite music with the rhythm 140 bpm ten minutes before the test Wingate were, increased peak anaerobic power in 5 seconds First Was seen.…”
Section: Introductionmentioning
confidence: 99%
“…Music during exercises has also been shown to increase the peak power of the LE [9], the endurance [10] and the motivation [11] in healthy persons. While simple rhythmic sound or existing music in the above studies may be suitable for these movements, purposely composed music that corresponds to the key features of a movement may be necessary for other movements such as STS.…”
Section: Introductionmentioning
confidence: 99%